BUMDes as a Driving Force of Rural Economy: The Effectiveness of Governance in Enhancing Village Original Revenue in Kadundung, Tana Toraja - Said, Siti Nur Reskiyawati; Le’torara, Henrika (Kunuz: Journal of Islamic Banking and Finance, 2025)
This study aims to identify the factors influencing the effectiveness of Village-Owned Enterprises (BUMDes) in enhancing Village Original Revenue (PAD) and to analyze the role of BUMDes in increasing the PAD of Kadundung Village. The research employs a qualitative method through observation, in-depth interviews, and documentation. The findings reveal that the development of BUMDes business units in Kadundung Village, supported by government and village funds, has generated substantial benefits for the community. BUMDes contributes to the growth of PAD while simultaneously assisting low-income households through micro-loan services. In addition, BUMDes has created employment opportunities and facilitated entrepreneurial activities by providing initial capital through cooperative-based financing schemes. Nevertheless, the effectiveness of BUMDes varies across its business units. The kiosk unit demonstrates significant effectiveness in enhancing PAD and improving community welfare, whereas the savings and loan cooperative unit faces challenges due to repayment defaults among villagers. Overall, BUMDes in Kadundung Village can be considered effective, particularly through the kiosk unit, although improvements in the management of the savings and loan cooperative are necessary to maximize its contribution